(untitled) (Research, Society and Development, 2022)
The work sought to understand whether the updating of the current legislation maintained improvements in the fight against the practice of pyramid crime in Brazil. The law that deals with the subject is very outdated, not covering the technologies of the modern world and thus not being applied efficiently in today’s society. The present research brings to the discussion what would be the most efficient methods and means to try to curb the practice in Brazil, and how the legislative update has a very important role, since the current legislation cannot be efficient in dealing with the illicit. For this purpose, the methodology of systematic literature review was used, in order to analyze whether in fact the legislative update would be more efficient. The work completed, which any legally well-designed legislation, tends to be more effective than it is current, and therefore can mitigate the best way of committing the illicit.